2020
DOI: 10.1021/acs.jpcc.0c01551
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity-Dependent Distinct Frictional Behaviors of Different Modified MXene Nanosheets

Abstract: MXene nanosheets are promising to be ultrathin solid lubricant or interface solving the friction and wear problems of miniaturized equipment. Here, the frictional behaviors and adhesive properties of the Ti 3 C 2 , F-Ti 3 C 2 , and TMA-Ti 3 C 2 nanosheets were explored by atomic force microscope for the first time. The nanofrictional behavior of TMA-Ti 3 C 2 was significantly different from that of Ti 3 C 2 and F-Ti 3 C 2 . The friction of TMA-Ti 3 C 2 increased slightly and then decreased as the load decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Atomic and friction force microscopy studies using multilayer powder as well as single-to few-layer MXenes have demonstrated their overall ability to reduce friction at the nanoscale. [119,120] Ti 3 C 2 T x MXenes etched via different routes (HF, HCl-LiF, and TMAOH delamination) demonstrated notable differences regarding their pull-off and slide-off forces as well as contact angles and work of adhesion, which were connected to the changes in their surface terminations. [120] Very recently, Nb 2 CT x MXenes have shown lower frictional and adhesive forces compared to Ti 3 C 2 T x , which were connected to their different atomic compositions thus inducing differences in the surface dipole moment densities.…”
Section: Tribological Behavior Of Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic and friction force microscopy studies using multilayer powder as well as single-to few-layer MXenes have demonstrated their overall ability to reduce friction at the nanoscale. [119,120] Ti 3 C 2 T x MXenes etched via different routes (HF, HCl-LiF, and TMAOH delamination) demonstrated notable differences regarding their pull-off and slide-off forces as well as contact angles and work of adhesion, which were connected to the changes in their surface terminations. [120] Very recently, Nb 2 CT x MXenes have shown lower frictional and adhesive forces compared to Ti 3 C 2 T x , which were connected to their different atomic compositions thus inducing differences in the surface dipole moment densities.…”
Section: Tribological Behavior Of Mxenesmentioning
confidence: 99%
“…[119,120] Ti 3 C 2 T x MXenes etched via different routes (HF, HCl-LiF, and TMAOH delamination) demonstrated notable differences regarding their pull-off and slide-off forces as well as contact angles and work of adhesion, which were connected to the changes in their surface terminations. [120] Very recently, Nb 2 CT x MXenes have shown lower frictional and adhesive forces compared to Ti 3 C 2 T x , which were connected to their different atomic compositions thus inducing differences in the surface dipole moment densities. [121] MXenes have been used as reinforcement phase in polymer composites to improve their mechanical and tribological properties.…”
Section: Tribological Behavior Of Mxenesmentioning
confidence: 99%
“…In Figure 3 c,d MXene flakes are also present inside the polymer matrix. Due to the hydrophilic nature of the 2D Ti 3 C 2 T x MXene flakes [ 59 ] they effectively blend with the chitosan-hyaluronate matrix. Therefore, they disperse throughout the entire volume of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Novel fabrication methods could give rise to more abundant functional groups, such as À Cl and À Li, and the diversity of MXene crystal structures, which also provide the flexibilities of manipulating the properties of MXene by changing the composition and distribution of surface groups. [22,23] Electronic properties of MXene depend on the type of metal elements, X elements and surface functional groups. Researches on Ti 3 C 2 MXene are extensive, focusing on the following three major systems: 1) Covalent surface modification [24,25] and defects introduction, [26,27] such as by removing Ti atoms or decorating various chemical groups.…”
Section: Introductionmentioning
confidence: 99%
“…MXene shows an excellent ability in performance control through successfully inducing metal nanoparticles, surface defects or polymers [19–21] . Novel fabrication methods could give rise to more abundant functional groups, such as −Cl and −Li, and the diversity of MXene crystal structures, which also provide the flexibilities of manipulating the properties of MXene by changing the composition and distribution of surface groups [22,23] …”
Section: Introductionmentioning
confidence: 99%